Thermo-mechanical analysis of free convection in an octagonal cavity with adjustable active walls and flexible separator - Mohamed Boujelbene; Awatef Abidi; S. A. M. Mehryan; Sultan Alshehery; Ahmad Hajjar; Nehad Ali Shah; Ibrahim Mahariq; Nidhal Ben Khedher (Scientific Reports)
Abstract This study investigates free convective within an octagonal cavity, which is partitioned into two compartments by a flexible separator. One of the left walls is maintained at a high temperature, while a lower temperature is applied to one of the right walls. The position of these active walls is adjustable, and the separator can be oriented vertically or inclined with either a positive or negative slope. The deformation of the flexible separator is modeled using the Arbitrary Lagrangian–Eulerian method. The outcomes indicate that locating the hotter wall near the top and moving the colder wall downwards hinders free convection and reduces the stress in the separator. Moreover, upward movement of both active walls leads to a decrease in the average temperature. An inclined separator with a positive slope enhances the heat transfer rate and experiences the lowest stress levels compared to vertical and negatively sloped separators. Raising Rayleigh number enhances the flow intensity and the stress in the flexible separator. Furthermore, it is found that a decrease in the elasticity modules of the separator from 1014 to 5 × 1011 results in a 5% increase in the average Nusselt number.